BUSPIRONE HYDROCHLORIDE EFFECTS ON CLINICAL AND FUNCTIONAL STATE IN PATIENTS WITH CHRONIC HEART FAILURE AND MIXED ANXIETY-DEPRESSIVE DISORDER - M. A. Khristichenko (Медицинский вестник Юга России, 2017)
Purpose: the assessment of buspirone hydrochloride effect on clinical and functional state in patients with chronic heart failure (CHF) and mixed anxiety-depressive disorder (MADD).Materials and method: the study included 49 patients with heart failure of ischemic etiology and MADD. Patients in Group 1 (n=25) received buspirone hydrochloride (in the starting dose of 15 mg/day with a gradual (within 2 weeks) increasing to the effective (30 mg/day)) in addition to standard CHF and coronary heart disease (CHD) therapy. Patients in group 2 (n=24) received standard therapy of CHF and CHD. After 6 months, we evaluated clinical and functional state in patients from both groups.Result: a statistically significant improvement in clinical and functional status (functional class of heart failure, physical exercise tolerance) were observed in patients with CHF and MADD in group of patients, who received buspirone hydrochloride in addition to standard therapy.Conclusion: buspirone hydrochloride admission in addition to standard therapy is associated with clinical and functional state improvement in patients with CHF and MADD.